Критерий промежуточного роста самоподобных групп - Леонов, Ю.Г. (Видавничий дім "Академперіодика" НАН України, 2007)
A new method for the upper estimation of growth for some infinite groups of the automorphisms of trees is investigated. A criterion which distinguishes when a group has exponential growth or subexponential is established.